The Combined Effect of Downregulated RB1 and Overexpressed lncRNA SSTRS-AS1 on Prediction Time to Castration-Resistant Prostate Cancer: Indonesian Cohort Studies - Soerohardjo, Indrawarman (AVES, 2022)
Objective: Identifying the mechanism underlying the initiation and development of castration-resistant prostate cancer remains challenging. Time to castration-resistant prostate cancer is defined by prostate-specific antigen progression and may represent a risk factor for developing immune alterations with a negative prognostic role in the overall survival of patients with prostate cancer. This study aimed to evaluate the combined effect of downregulated RB1 and overexpressed SSTR5-AS1 as biomarkers for predicting time to castration-resistant prostate cancer. Material and Methods: The clinical and pathological data of patients with prostate cancer were collected retrospectively. Between 2015 and 2019, a total of 36 patients who received castration were included. Expressions of mRNA of RB1 and SSTR5-AS1 from primary tumors were quantified using quantitative real-time polymerase chain reaction. Patients were divided into 2 groups: the first group consisted of patients with Rb1 expression lower than the median and expression of SSTRS5-AS1 higher than the median, and the second group consisted of all the other patients. This study was conducted in compliance with the latest Helsinki Declaration and registered on Elsevier International Standard Randomized Controlled trial number registry. Results: In this study, patients with both downregulated RB1 and overexpressed Long non-coding RNAs (lncRNA) SSTR5-AS1 showed shorter time to castration-resistant prostate cancer (mean 23.6 ± 3.3 months) compared to other groups (mean 38.3 ± 4.9 months) (log-rank test, P = .028). Conclusion: The combination of downregulation of RB1 and overexpression of SSTR5-AS1 is a strong predictor of shorter time to castration-resistant prostate cancer in the Indonesian population. Additionally, patients with International Society of Urological Pathology (ISUP) score >4 did not demonstrate this predictive value on time to castration-resistant prostate cancer.